2020
DOI: 10.1111/jgh.15286
|View full text |Cite
|
Sign up to set email alerts
|

Dose–response association of the ZJU index and fatty liver disease risk: A large cohort in China

Abstract: Aim The aim of this study is to investigate the sex‐specific association between the ZJU index and risk of fatty liver disease in a large Chinese cohort. Methods A total of 28 729 adults without fatty liver disease at baseline and who completed at least one follow‐up of annual examinations between 2009 and 2016 were included in this study. The Cox proportional hazards model was used to estimate hazard ratios (HRs) and 95% confidence intervals (CI) for fatty liver disease risk associated with the ZJU index. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The estimated glomerular filtration rate (eGFR) was calculated by the Cockcroft-Gaulu equation: eGFR = [140-age (years)] × body weight (kg) × 1.23/Cr (μmol/L) (× 0.85 if female). The powerful surrogate marker for fatty liver disease, Zhejiang University (ZJU) index, was calculated by BMI (kg/m 2 ) + FBG (mmol/L)+ TG (mmol/L)+ 3 × ALT (U/L)/AST (U/L) (+2 if female) ( 25 ). The fibrosis-4 (FIB4) index was defined as: age (years) × AST (U/L)/(platelet count (10 9 /L) × √ ALT (U/L)] ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…The estimated glomerular filtration rate (eGFR) was calculated by the Cockcroft-Gaulu equation: eGFR = [140-age (years)] × body weight (kg) × 1.23/Cr (μmol/L) (× 0.85 if female). The powerful surrogate marker for fatty liver disease, Zhejiang University (ZJU) index, was calculated by BMI (kg/m 2 ) + FBG (mmol/L)+ TG (mmol/L)+ 3 × ALT (U/L)/AST (U/L) (+2 if female) ( 25 ). The fibrosis-4 (FIB4) index was defined as: age (years) × AST (U/L)/(platelet count (10 9 /L) × √ ALT (U/L)] ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…In another cohort involving 28,729 Chinese adults without fatty liver disease at baseline, the ZJU index was found to be significantly associated with an elevated risk of developing fatty liver disease over a median follow-up of 3.01 years. As the ZJU quartiles increased, the HRs increased correspondingly, with 4.87 (4.24-5.59) for women and 6.23 (5.56-6.98) men (12). Moreover, validation in North American settings was evident in a study involving 107 obese women, which revealed an AUC of 0.742 for the ZJU index, emphasizing its applicability in predicting NAFLD among this population (10).…”
Section: Discussionmentioning
confidence: 92%
“…Conversely, this interaction was not significant in the population under 50 years. In the research by Li et al (12), the findings revealed a higher HR for men, at 6.23 (5.56-6.98), compared to women, who had an HR of 4.87 (4. 24-5.59).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In both the derivation and validation cohorts, the AUROC of FFI was better than that of anthropometric parameters (BMI and WC) that are closely related to fatty liver disease and better than that of other NAFLD diagnosis scores (FLI, his, and ZJU) that have been proven to have good diagnostic value for NAFLD. [27][28][29] More studies are needed to assess noninvasive scoring models for MAFLD in the future.…”
Section: Discussionmentioning
confidence: 99%